Efeitos de diferentes frequências da estimulação elétrica nervosa transcutănea em relação à acomodação e à agradabilidade - Silva, Danilo de Oliveira [UNESP]; Ferreira, Amanda Schenatto; Gonçalves, Ana Valéria; Costa, Marina Dalla; Zilio, Marina; Fréz, Andersom Ricardo; Bertolini, Gladson Ricardo Flor (My University, 2014)
Aims: The aim of this study was to investigate the effects of different frequencies of transcutaneous electrical nerve stimulation (TENS) regarding to accommodation and pleasantness of the different forms of application. Methods: The sample consisted of 20 subjects randomly divided into 3 groups, in which they were submitted to 3 different frequencies of TENS: 7 Hz, 100Hz, 255Hz, pulse duration of 250 μs, for 20 minutes once a week over three weeks. The volunteers were instructed to indicate the first and subsequent accommodation moments. At the end of the period of data collection, subjects were asked about which frequency they thought most enjoyable. Results: For the threshold of adaptation, considering all frequencies analyzed, it was found that there was no significant difference (p> 0.05), a fact that was also repeated for the number of adaptations in 20 minutes (p> 0.05). With regard to pleasantness, 11 subjects indicated the frequency of 7 Hz as the most enjoyable. Conclusions: There was no significant difference in threshold for adaptation and the number of adaptations between the frequencies used. The frequency of 7 Hz was identified as the most enjoyable then the frequency of 100 Hz.
Effects of different transcutaneous electrical nerve stimulation frequencies regarding adaptation and pleasantness
Keywords: Perception of touch; Physical therapy modalities; Transcutaneous electrical nerve stimulation